GEOEPIDEMIOLOGICAL ASPECTS OF LEPROSY IN CHILDREN UNDER 15 YEARS IN THE STATE OF MARANHÃO, FROM 2010 TO 2021 - Moreira, Rodolfo José de Oliveira (2024)
Objective: To analyze the global spatial autocorrelation and the local indicator of spatial association and determine the trend of new cases of leprosy in children under 15 years of age in the state of Maranhão and in the Regional Health Units (RHUs) from 2010 to 2021. Method - Ecological time series study, with separate analyses, using data from the Notifiable Diseases Information System. The trend of new cases of the event was analyzed by Prais-Winsten regression. To perform the spatial analysis of the data, the cumulative frequency of cases was calculated and divided into 3 four-year periods, and the Global Moran Index and Local Moran Index (LISA) were used. Results: 3.834 cases were analyzed. The detection trend of new cases was decreasing in the state of Maranhão and in 8 RHUs, remaining stable in the others. The spatial analysis showed positive spatial autocorrelation by the Global Moran Index in the 3 quadrenniums, and LISA showed significance and clustered municipalities in all 3 quadrennia. Conclusion: The trend of new cases was decreasing in eight RHUs and in the state, and stable in the other RHUs. There is a positive autocorrelation of the annual detection coefficient and the presence of high-risk clusters in the state.